Survey Karakteristik Demografi Petugas Rekam Medis di Puskesmas Wilayah Kota Mataram - Ikhtiar, Rian Wahyul; Hasanah, Uswatun; Ikhwan, Ikhwan; Putra, Rizal Pratama Adi; Susilo, Beny Binarto Budi; Halid, Musparlin; Permana, Yan Reiza; Gazali, Muhammad Munawir (LP2M IIK (Lembaga Penelitian dan Pengabdian Masyarakat Institut Ilmu Kesehatan) Bhakti Wiy, 2024)
Characteristics of Medical Record officers consist of religion, age, gender, years of service, education, training, and employment status. This research was conducted at the Public Health Center in the City of Mataram. The purpose of this study was to determine the characteristics of medical record officers at the public health center in the city of Mataram. The design of this research is descriptive. The sample in this study were all medical record officers at the Mataram City of Health Center, totaling 39 medical record officers. The results showed that the medical record officers at the Mataram City of Health Center were mostly Muslim (100.0%), the sex of the officers was female as many as 22 people (56.4%), and the service period of the officers was less than 5 years (48,7%), Officer education is Diploma III of Medical Record and Health Information (MRHI) as many as 12 people (30.8%), training officers who have never attended training as many as 28 people (71.8%), while the staffing status of non-civil servant officers is 23 people (59, 0%). The conclusion is there needs to be an increase in the number and quality of medical record personnel in health centers with a Diploma III MRHI background